Simulations of tip vortex cavitation flows with nonlinear k-ε model. (November 2015) - Wang, Benlong; Liu, Zhihui; Peng, Xiaoxing; Liu, Dengcheng
Abstract: Effects of turbulence models on the simulations of tip vortex wetted flows and cavitating flows are studied. Two types RANS turbulence models, with and beyond the Boussinesq turbulent-viscosity hypothesis, are investigated by examining experimental results regarding strain rate and Reynolds shear stress distributions in the vortex region. The numerical results imply that the spatial phase shift between the mean strain rate and Reynolds stresses can be accurately modeled by the nonlinear k-ε turbulence model; the tip vortex cavitation region can only be predicted using the nonlinear turbulence model. The mechanism of the over-dissipation due to the turbulence model is analyzed in terms of the turbulence production, which is one of the dominant source terms in the transport equations of energy. The numerical results imply that the nonlinear k-ε model is a promising candidate for predicting tip vortex cavitation flows in practical applications at a reasonable computational cost.